Ekstensi TAM untuk Memprediksi Niat Menggunakan E-Money di Pontianak - Irawan Wingdes (UNIVERSITAS AMIKOM YOGYAKARTA, 2018)
E-money berbasis smart card diwajibkan pemerintah daerah sejak tahun 2018 untuk pengisian bahan bakar tetapi publikasi data sekunder menunjukkan hasil tidak sesuai harapan. Penelitian kuantitatif ini bertujuan untuk memprediksi niat menggunakan e-money dengan mengekstensikan rational choice theory dengan faktor benefit of compliance, cost of compliance, cost of non compliance dan perceived speed pada technology acceptance model. Data dikumpulkan dengan survei menggunakan kuesioner, data diolah dan hipotesis diuji dengan structural equation modeling berbasis partial least square. Jumlah sampel dengan purposive method yang dikumpulkan adalah 336 responden (slovin) dengan margin of error 5% untuk populasi pengguna kendaraan di Pontianak. Pengujian menunjukkan faktor yang digunakan valid dan reliabel, dengan hasil: transaction speed, perceived ease of use, perceived usefulness, benefit of compliance, cost of compliance, cost of non compliance mempengaruhi behavioral intention. Faktor yang mempengaruhi paling kuat niat menggunakan adalah cost of non compliance dan perceived transaction speed. Hasil menunjukkan pengguna akan berniat menggunakan e-money bila diwajibkan dan disertai dengan sanksiKata kunci—E-money, Ekstensi TAM, Rational Choice Theory, Behavioral IntentionSmart card based e-money was required by local authorities since 2018 for refueling activity in Pontianak but results were not as expected. Therefore, this quantitative study aims to predict intention to use e-money by extending rational choice theory with its antecedents: benefit of compliance, cost of noncompliance, cost of compliance and perceived transaction speed to technology acceptance model. Data for analysis was acquired using questionaire based survey. Hypotheses are tested by utilizing partial least square based structural equation modeling. A total of 336 samples (slovin) from total vehicles owners in Pontianak are acquired using purposive method with margin of error of 5%. Test results shows antecedents extended to TAM are valid and reliable with transaction speed, perceived ease of use, perceived usefulness, benefit of compliance, cost of compliance, cost of non compliance significantly influences intention to use. Factors with greatest influence are cost of non compliance and transaction speed. Results suggest user’s intention to use e-money in mandatory situation are influenced strongly only when there are consequences imposed at non compliance.Key words—E-money, extended TAM, Rational Choice Theory,Behavioral Intention